Bc. log a - log b = log (a/b) than use this formula will get
log x^2 -log x = log (x^2 /x) = log x so choice D. is right sure
hope helped
Subtract what is to the right of the equal sign form both side of the equation but any way the answer is 0
Answer:
<em>C.</em> ![(5-\frac{1}{2})^6](https://tex.z-dn.net/?f=%285-%5Cfrac%7B1%7D%7B2%7D%29%5E6)
Step-by-step explanation:
Given
![15(5)^2(-\frac{1}{2})^4](https://tex.z-dn.net/?f=15%285%29%5E2%28-%5Cfrac%7B1%7D%7B2%7D%29%5E4)
Required
Determine which binomial expansion it came from
The first step is to add the powers of he expression in brackets;
![Sum = 2 + 4](https://tex.z-dn.net/?f=Sum%20%3D%202%20%2B%204)
![Sum = 6](https://tex.z-dn.net/?f=Sum%20%3D%206)
Each term of a binomial expansion are always of the form:
![(a+b)^n = ......+ ^nC_ra^{n-r}b^r+.......](https://tex.z-dn.net/?f=%28a%2Bb%29%5En%20%3D%20......%2B%20%5EnC_ra%5E%7Bn-r%7Db%5Er%2B.......)
Where n = the sum above
![n = 6](https://tex.z-dn.net/?f=n%20%3D%206)
Compare
to the above general form of binomial expansion
![(a+b)^n = ......+15(5)^2(-\frac{1}{2})^4+.......](https://tex.z-dn.net/?f=%28a%2Bb%29%5En%20%3D%20......%2B15%285%29%5E2%28-%5Cfrac%7B1%7D%7B2%7D%29%5E4%2B.......)
Substitute 6 for n
![(a+b)^6 = ......+15(5)^2(-\frac{1}{2})^4+.......](https://tex.z-dn.net/?f=%28a%2Bb%29%5E6%20%3D%20......%2B15%285%29%5E2%28-%5Cfrac%7B1%7D%7B2%7D%29%5E4%2B.......)
[Next is to solve for a and b]
<em>From the above expression, the power of (5) is 2</em>
<em>Express 2 as 6 - 4</em>
![(a+b)^6 = ......+15(5)^{6-4}(-\frac{1}{2})^4+.......](https://tex.z-dn.net/?f=%28a%2Bb%29%5E6%20%3D%20......%2B15%285%29%5E%7B6-4%7D%28-%5Cfrac%7B1%7D%7B2%7D%29%5E4%2B.......)
By direct comparison of
![(a+b)^n = ......+ ^nC_ra^{n-r}b^r+.......](https://tex.z-dn.net/?f=%28a%2Bb%29%5En%20%3D%20......%2B%20%5EnC_ra%5E%7Bn-r%7Db%5Er%2B.......)
and
![(a+b)^6 = ......+15(5)^{6-4}(-\frac{1}{2})^4+.......](https://tex.z-dn.net/?f=%28a%2Bb%29%5E6%20%3D%20......%2B15%285%29%5E%7B6-4%7D%28-%5Cfrac%7B1%7D%7B2%7D%29%5E4%2B.......)
We have;
![^nC_ra^{n-r}b^r= 15(5)^{6-4}(-\frac{1}{2})^4](https://tex.z-dn.net/?f=%5EnC_ra%5E%7Bn-r%7Db%5Er%3D%2015%285%29%5E%7B6-4%7D%28-%5Cfrac%7B1%7D%7B2%7D%29%5E4)
Further comparison gives
![^nC_r = 15](https://tex.z-dn.net/?f=%5EnC_r%20%3D%2015)
![a^{n-r} =(5)^{6-4}](https://tex.z-dn.net/?f=a%5E%7Bn-r%7D%20%3D%285%29%5E%7B6-4%7D)
![b^r= (-\frac{1}{2})^4](https://tex.z-dn.net/?f=b%5Er%3D%20%28-%5Cfrac%7B1%7D%7B2%7D%29%5E4)
[Solving for a]
By direct comparison of ![a^{n-r} =(5)^{6-4}](https://tex.z-dn.net/?f=a%5E%7Bn-r%7D%20%3D%285%29%5E%7B6-4%7D)
![a = 5](https://tex.z-dn.net/?f=a%20%3D%205)
![n = 6](https://tex.z-dn.net/?f=n%20%3D%206)
![r = 4](https://tex.z-dn.net/?f=r%20%3D%204)
[Solving for b]
By direct comparison of ![b^r= (-\frac{1}{2})^4](https://tex.z-dn.net/?f=b%5Er%3D%20%28-%5Cfrac%7B1%7D%7B2%7D%29%5E4)
![r = 4](https://tex.z-dn.net/?f=r%20%3D%204)
![b = \frac{-1}{2}](https://tex.z-dn.net/?f=b%20%3D%20%5Cfrac%7B-1%7D%7B2%7D)
Substitute values for a, b, n and r in
![(a+b)^n = ......+ ^nC_ra^{n-r}b^r+.......](https://tex.z-dn.net/?f=%28a%2Bb%29%5En%20%3D%20......%2B%20%5EnC_ra%5E%7Bn-r%7Db%5Er%2B.......)
![(5+\frac{-1}{2})^6 = ......+ ^6C_4(5)^{6-4}(\frac{-1}{2})^4+.......](https://tex.z-dn.net/?f=%285%2B%5Cfrac%7B-1%7D%7B2%7D%29%5E6%20%3D%20......%2B%20%5E6C_4%285%29%5E%7B6-4%7D%28%5Cfrac%7B-1%7D%7B2%7D%29%5E4%2B.......)
![(5-\frac{1}{2})^6 = ......+ ^6C_4(5)^{6-4}(\frac{-1}{2})^4+.......](https://tex.z-dn.net/?f=%285-%5Cfrac%7B1%7D%7B2%7D%29%5E6%20%3D%20......%2B%20%5E6C_4%285%29%5E%7B6-4%7D%28%5Cfrac%7B-1%7D%7B2%7D%29%5E4%2B.......)
Solve for ![^6C_4](https://tex.z-dn.net/?f=%5E6C_4)
![(5-\frac{1}{2})^6 = ......+ \frac{6!}{(6-4)!4!)}*(5)^{6-4}(\frac{-1}{2})^4+.......](https://tex.z-dn.net/?f=%285-%5Cfrac%7B1%7D%7B2%7D%29%5E6%20%3D%20......%2B%20%5Cfrac%7B6%21%7D%7B%286-4%29%214%21%29%7D%2A%285%29%5E%7B6-4%7D%28%5Cfrac%7B-1%7D%7B2%7D%29%5E4%2B.......)
![(5-\frac{1}{2})^6 = ......+ \frac{6!}{2!!4!}*(5)^{6-4}(\frac{-1}{2})^4+.......](https://tex.z-dn.net/?f=%285-%5Cfrac%7B1%7D%7B2%7D%29%5E6%20%3D%20......%2B%20%5Cfrac%7B6%21%7D%7B2%21%214%21%7D%2A%285%29%5E%7B6-4%7D%28%5Cfrac%7B-1%7D%7B2%7D%29%5E4%2B.......)
![(5-\frac{1}{2})^6 = ......+ \frac{6*5*4!}{2*1*!4!}*(5)^{6-4}(\frac{-1}{2})^4+.......](https://tex.z-dn.net/?f=%285-%5Cfrac%7B1%7D%7B2%7D%29%5E6%20%3D%20......%2B%20%5Cfrac%7B6%2A5%2A4%21%7D%7B2%2A1%2A%214%21%7D%2A%285%29%5E%7B6-4%7D%28%5Cfrac%7B-1%7D%7B2%7D%29%5E4%2B.......)
![(5-\frac{1}{2})^6 = ......+ \frac{6*5}{2*1}*(5)^{6-4}(\frac{-1}{2})^4+.......](https://tex.z-dn.net/?f=%285-%5Cfrac%7B1%7D%7B2%7D%29%5E6%20%3D%20......%2B%20%5Cfrac%7B6%2A5%7D%7B2%2A1%7D%2A%285%29%5E%7B6-4%7D%28%5Cfrac%7B-1%7D%7B2%7D%29%5E4%2B.......)
![(5-\frac{1}{2})^6 = ......+ \frac{30}{2}*(5)^{6-4}(\frac{-1}{2})^4+.......](https://tex.z-dn.net/?f=%285-%5Cfrac%7B1%7D%7B2%7D%29%5E6%20%3D%20......%2B%20%5Cfrac%7B30%7D%7B2%7D%2A%285%29%5E%7B6-4%7D%28%5Cfrac%7B-1%7D%7B2%7D%29%5E4%2B.......)
![(5-\frac{1}{2})^6 = ......+15*(5)^{6-4}(\frac{-1}{2})^4+.......](https://tex.z-dn.net/?f=%285-%5Cfrac%7B1%7D%7B2%7D%29%5E6%20%3D%20......%2B15%2A%285%29%5E%7B6-4%7D%28%5Cfrac%7B-1%7D%7B2%7D%29%5E4%2B.......)
![(5-\frac{1}{2})^6 = ......+15(5)^{6-4}(\frac{-1}{2})^4+.......](https://tex.z-dn.net/?f=%285-%5Cfrac%7B1%7D%7B2%7D%29%5E6%20%3D%20......%2B15%285%29%5E%7B6-4%7D%28%5Cfrac%7B-1%7D%7B2%7D%29%5E4%2B.......)
![(5-\frac{1}{2})^6 = ......+15(5)^2(\frac{-1}{2})^4+.......](https://tex.z-dn.net/?f=%285-%5Cfrac%7B1%7D%7B2%7D%29%5E6%20%3D%20......%2B15%285%29%5E2%28%5Cfrac%7B-1%7D%7B2%7D%29%5E4%2B.......)
<em>Check the list of options for the expression on the left hand side</em>
<em>The correct answer is </em>
<em />
<h2><em>each student requires 9m² of floor </em></h2><h2><em>and given the no. of students is 50
</em></h2><h2><em>So the total area of the room is 9m²X50=450m²
</em></h2><h2><em>Given the length of the room is 25m
</em></h2><h2><em>so the Breadth is =450/25=18m
</em></h2><h2><em>
</em></h2><h2><em>each student requires 108m³ of space </em></h2><h2><em>so total volume of the room is 108X50=5400m³
</em></h2><h2><em>we know that : Volume=Area X h
</em></h2><h2><em> so⇒5400=450Xh
</em></h2><h2><em> ⇒h=5400/450= 12m</em></h2><h2><em /></h2><h2><em>HOPE IT HELPS (◕‿◕✿)</em></h2>
Answer:
I'm afraid that none of them are, as the x-intercepts of the equation are 0 and 9 respectively
however, D. is the closest to it, and it would be the correct graph if there were parentheses around ![x^{2}-6x](https://tex.z-dn.net/?f=x%5E%7B2%7D-6x)
Step-by-step explanation: